Folic acid supplementation during preconception period in sub-Saharan African countries: A systematic review and meta-analysis - Mekuriaw Nibret Aweke; Elsa Awoke Fentie; Muluken Chanie Agimas; Lemlem Daniel Baffa; Ever Siyoum Shewarega; Aysheshim Kassahun Belew; Esmael Ali Muhammad; Berhanu Mengistu (PLoS ONE, 2025)
Introduction Neural tube defects (NTDs) are serious congenital anomalies of the central nervous system caused by disruptions in early embryonic development. The prevalence is about twice as common in low- and middle-income countries and more prevalent in sub-Saharan Africa. Folic acid deficiency is a major risk factor and common during pregnancy. However, limited research on preconception folic acid supplementation in this region highlights the need for systematic reviews and targeted interventions to improve maternal and fetal health. Methods We conducted a systematic literature search in EMBASE, MEDLINE, Scopus, CINAHL, Google Scholar, and Google for studies on the proportion of folic acid supplementation during the preconception period, covering publications up to January 2024. Study quality was assessed using the Newcastle-Ottawa Scale. Heterogeneity was evaluated with Cochrane Q and I2 statistics, and small study effects were tested with Egger’s test at a 5% significance level. The certainty of evidence was assessed using the GRADE approach. A random-effects model was used to estimate the pooled proportion of FA supplementation during the preconception period in sub-Saharan African countries. Result This systematic review included 28 studies with a total of 12,562 participants. The highest (45.2%) and lowest (1.9%) proportion of folic acid supplementation during preconception period were recorded in the southern and Amhara regions of Ethiopia, respectively. The estimated pooled proportion of folic acid supplementation among women in Sub-Saharan Africa (SSA) during preconception period was (14.10%; 95% CI: 11.22–16.98) with significant heterogeneity between studies (I2 = 97.71%, p = 0.001). In sub-group analysis based on corresponding countries the highest estimated folic acid supplementation proportion during preconception period was found in studies conducted in Kenya ((22%; 95% CI: 19%-25%), I2 = 97.7%), followed by studies conducted in Ghana (20%; 95% CI: 7%-33%), I2 = 96.9%). The majority of the studies included in the analysis are of high quality, with quality scores ranging from 7 to 8. The certainty of evidence was assessed using the GRADE approach, resulting in a low overall rating. Conclusion The results of this systematic review and meta-analysis indicated that folic acid supplementation during preconception period is significantly low among mothers in sub-Saharan African countries, despite being one of the best approaches to improve birth outcomes. Therefore, healthcare organizations, governments, policymakers, and other stakeholders involved in folic acid supplementation must collaborate on developing strategies to improve its uptake during the preconception period.